A history of the French in London Liberty, equality, opportunity - Kelly, Debra; Cornick, Martyn (IHR Conference Series, 2013)
This book examines, for the first time, the history of the social, cultural, political and economic presence of the French in London, and explores the multiple ways in which this presence has contributed to the life of the city. The capital has often provided a place of refuge, from the Huguenots in the 17th century, through the period of the French Revolution, to various exile communities during the 19th century, and on to the Free French in the Second World War.It also considers the generation of French citizens who settled in post-war London, and goes on to provide insights into the contemporary French presence by assessing the motives and lives of French people seeking new opportunities in the late 20th and early 21st centuries. It analyses the impact that the French have had historically, and continue to have, on London life in the arts, gastronomy, business, industry and education, manifest in diverse places and institutions from the religious to the political via the educational, to the commercial and creative industries.